1999
DOI: 10.1136/mp.52.6.357
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of FISH signals using intermittent microwave irradiation for analysis of chromosomal instability in gastric cancer

Abstract: Gastrointestinal tract tumours are notorious for their diYculty in relation to conventional cytogenetic analysis. In particular, necrosis, the presence of stromal inflammatory and other cells, and poor attachment of tumour cells have led to problems with the quality and reliability of cytogenetic preparations, even with the recently developed fluorescence in situ hybridisation (FISH) technique. Furthermore, background autofluorescence masks the weak hybridisation signals in the nuclei. To overcome this problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The use of an AR approach was initiated based on evidence that formalin-induced modification of protein and of nucleic acid is similar von Hippel 1977a, 1977b;Masuda et al 1999;Shi et al 2001). Experimental evidence was forthcoming in support of this approach, describing remarkable improvement of signal for chromogenic in situ hybridization (CISH) and FISH (Oliver et al 1997;Bull and Harnden 1999;Kitayama et al 1999;Gu et al 2000). In addition, other investigators have demonstrated the effectiveness of heating for extraction of nucleic acids from FFPE tissues.…”
Section: Extraction Of Nucleic Acids and Proteins From Ffpe Tissuesmentioning
confidence: 99%
“…The use of an AR approach was initiated based on evidence that formalin-induced modification of protein and of nucleic acid is similar von Hippel 1977a, 1977b;Masuda et al 1999;Shi et al 2001). Experimental evidence was forthcoming in support of this approach, describing remarkable improvement of signal for chromogenic in situ hybridization (CISH) and FISH (Oliver et al 1997;Bull and Harnden 1999;Kitayama et al 1999;Gu et al 2000). In addition, other investigators have demonstrated the effectiveness of heating for extraction of nucleic acids from FFPE tissues.…”
Section: Extraction Of Nucleic Acids and Proteins From Ffpe Tissuesmentioning
confidence: 99%
“…The heat-induced retrieval approach has also been applied to in situ hybridization (ISH), TUNEL [terminal deoxynucleotidyl transferase (TdT)-mediated dUTP-biotin nick end-labeling], and FISH (fluorescence in situ hybridization)] (Bull and Harnden 1999;Kitayama et al 1999;Gu et al 2000;Lucassen et al 2000). For multiple IHC staining, heat was used between each round of the immunostaining procedure to block crossreactivity in addition to retrieval of antigenicity (Lan and Nikolic-Paterson 2000).…”
mentioning
confidence: 99%
“…5) [16]. We have also demonstrated that clearer probe-labeling of chromosome territories in FISH studies could be obtained on paraffin sections prepared by QF method without microwave treatment, though such probe-labeling was not always successful even with microwave treatment on paraffinembedded sections prepared by routine aldehyde fixation and alcohol-dehydration method [12,13,16]. These positive effects of QF could be obtained by conventional QF methods for resected tissues and also in the in vivo cryotechnique for living animal organs.…”
Section: Significance Of Cryotechniques For Immunohistochemistrymentioning
confidence: 86%